Do monopólio da terra ao monopólio digital: uma análise do colonialismo de digital e de dados em área de assentamento da reforma agrária - Wioppiold, Kauã Arruda (2023)
The advancement of connectivity is changing the dimensions of territories, mainly due to the actions of capital, resulting in crises. With the advancement of the technical-scientific-informational environment, new tools emerge that accelerate globalization over the territories of agrarian reform, explore them, and maximize profit through what is called digital colonialism and/or data colonialism. This characterizes the era of surveillance capitalism, which can be understood as a new form of corporate colonization, converting all aspects of everyday life into profitable assets, similar to historical colonialism. Using the dialectical method and qualitative research, this study carries out a literature review and exploratory research to understand how digital and data colonialism affect agrarian reform territories. In this specific case, interviews were carried out in settlements of the Movimento dos Trabalhadores sem Terra in the city of Jóia, in Rio Grande do Sul. Companies that already hold large monopolies are using their platforms to expand rural connectivity, expand data collection, and generate highly profitable assets without there being a counterpoint through movements. Currently, in addition to conquering land, corporations are also colonizing digital technology. With this, it is necessary to overcome new forms of control through monopolies based on socio-territorial movements and field education movement.